OPTIMALISASI KOMUNIKASI INTERPERSONAL PEMIMPIN REDAKSI MALANG POST DALAM MENINGKATKAN ETOS KERJA - ISMANIYAH . (Universitas Tribhuwana Tunggadewi, 2015)
Abstract: Interpersonal communication is a very important communication conducted in a company to support the work ethic of his subordinates. As interpersonal communication that occurs in Malang Post print media companies. communication that occurs between the editor and the reporter is nurtured well. Because interpersonal communication is very important to apply for a work ethic and a supporter in exploring better news and actual.This study used descriptive qualitative research method steps of data collection through in-depth interviews with informants and documentation obtained through purposive sampling technique. To gauge the validity of the validity of the data is done by data triangulation techniques. From the steps of data analysis was performed using a model of interactive data analysis that includes process data reduction, data presentation and conclusion. From research carried out have been obtained keimpulan: interpersonal communication that occurs between editors and reporters Malang Post interwoven very good and harmonious. Interpersonal communication is one of the activities the editor in improving work ethic journalists, through good cooperation it will be built up a good relationship anyway. Keywords: interpersonalcommunication, Malang Post editors and reporters